1991
DOI: 10.1111/j.1365-2141.1991.tb04390.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminished AγT fetal globin levels in Sardinian haplotype II β°‐thalassaemia patients are associated with a four base pair deletion in the AγT promoter

Abstract: In Sardinia, the beta-39 nonsense mutation is the primary cause of beta 0-thalassaemia. This mutation is found mainly on beta-globin gene cluster haplotypes I and II, which differ in their A gamma globin types (A gamma I and A gamma T, respectively). This report presents data on G gamma, A gamma I and A gamma T levels, and the presence or absence of a 4 base pair (bp) deletion at -225 to -222 of the A gamma globin promoter, in 55 poly-transfused beta 0-thalassaemia major patients. Six patients were homozygotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…One or more of the deleted AGCA nucleotides seem to contribute to the binding of the trans-acting factor (Beldjord et al, 1992). Therefore, the 4-bp deletion is associated with a reduced expression of HBG1 (Harvey et al, 1992), and newborns with this deletion showed a decreased level of total HbF (Manca et al, 1991;Beldjord et al, 1992). The 4-bp deletion not only affects the expression of the A γ globin gene HBG1, but also that of the G γ globin gene HBG2 (Coleman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One or more of the deleted AGCA nucleotides seem to contribute to the binding of the trans-acting factor (Beldjord et al, 1992). Therefore, the 4-bp deletion is associated with a reduced expression of HBG1 (Harvey et al, 1992), and newborns with this deletion showed a decreased level of total HbF (Manca et al, 1991;Beldjord et al, 1992). The 4-bp deletion not only affects the expression of the A γ globin gene HBG1, but also that of the G γ globin gene HBG2 (Coleman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Diminished expression of A γ globin has been observed in subjects with a 4-basepair (bp) deletion of AGCA from nucleotide positions −222 to −225 in the promoter of the HBG1 gene (Gilman et al, 1988;Manca et al, 1991). This gene deletion affects the G γ: A γ ratio of both newborns and adults.…”
Section: Introductionmentioning
confidence: 99%
“…The sister (II-2) was a simple IVSII-745 heterozygote with a T at −158 of the G ␥ promoter in one of the two alleles and 3.7% HbF. Genetic and molecular studies (Table II) T expression [19] and, as was expected, they were found negative since it has been reported that the 4-bp deletion is associated with haplotype II.…”
Section: Resultsmentioning
confidence: 63%
“…The higher G␥/A␥ ratio was hypothesized to be due to a decreased A␥ expression resulted from the 4 bp deletion, but it may also be explained by that an increasing anemic stress preferentially stimulates the G␥-globin gene [12]. By analyzing quantitatively the globin chains in the ␤ 0 -thalassemia individuals who had higher HbF levels (HbF > 3%), Nanca and Gelman et al further proved that the expression level of the A␥-globin gene with the 4 bp deletion (A␥ T ) was lower than that of the normal A␥ gene lacking the 4 bp deletion [13]. In the normal adults, HbF is usually lower than 1% of the total Hb and the A␥/G␥+A␥ is about 60%.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal adults, HbF is usually lower than 1% of the total Hb and the A␥/G␥+A␥ is about 60%. In the ␤-thalassemia [11,13] cases, the A␥/G␥+A␥ was 33% [11] and 38% [13] that were indeed lower than the normal, but the HbF with A␥ type was still slightly higher than the normal adult (<0.6%) because the ␤-thalassemia patients had higher HbF levels. The exact mechanisms responsible for the high level of the G␥ and A␥ product in some ␤-thalassemia cases are not clear yet, nor have any cases been provided to show how the -225 to -222 deletion influences the the A␥-globin gene expression in the non-␤-thalssemia adult.…”
Section: Discussionmentioning
confidence: 99%